Measles vaccination in lung transplant candidates - Kostinov, Мikhail P.; Polishchuk, Valentina B.; Ryzhov, Аleksey А.; Zhuravlev, Pavel I.; Karchevskaya, Natalia A.; Tarabrin, Evgeniy A.; Solovieva, Irina L.; Cherdantsev, Alexander P.; Khrapunova, Izabella A.; Foshina, Elena P. (Frontiers in Immunology, 2025)
BackgroundThe incidence of measles is now increasing. Measles is especially dangerous for high-risk individuals, including lung transplant candidates with severe progressive bronchopulmonary disorders.ObjectiveThe objective of this study was to investigate how vaccine-induced immunity is developed in lung transplant candidates seronegative for measles. In order to study vaccine-induced measles immunity, the study subjects were divided in two groups. The main group consisted of 22 patients (11 males and 11 females) with severe bronchopulmonary disorders, aged 19 to 58. The control group was made up of healthcare providers who were matched with respect to age and gender to the patients in the main group. All study subjects were given a single dose of measles vaccine. Levels of anti-measles IgG antibodies (Ab) were measured by enzyme-linked immunosorbent assay (ELISA) using the VectoMeasles-IgG kit (Russia).ResultsOne month after vaccination, both study groups showed a statistically significant increase in anti-measles IgG Ab compared to baseline levels. In the main group, vaccine-induced Ab levels were significantly lower than in the control group (0.41 [0.098; 1.75] IU/mL vs. 1.94 [0.96; 3.3] IU/mL; р<0.0001). The rates of seroconversion were 73% and 100% in the main and control groups, respectively. The majority of non-responders (83%) in the main group had restrictive pulmonary disease. One year after vaccination, anti-measles Ab were detected in 36% (5/14) of the patients in the main group.ConclusionAdministration of a single dose of measles vaccine to seronegative lung transplant candidates with severe progressive bronchopulmonary disorders was safe and resulted in protective levels of antibodies in 73% of patients. One year after vaccination, anti-measles Ab were detected in 36% of the patients, which suggested that a single dose failed to induce a robust immune response in this patient population.